2022
DOI: 10.1177/02184923221094974
|View full text |Cite
|
Sign up to set email alerts
|

Early- and mid-term outcomes of reinterventions for aortic bioprosthesis failure

Abstract: Background The aim of this study was to evaluate early- and mid-term results of our actual practice embedding redo aortic valve replacement and transcatheter procedures for aortic bioprosthetic failure. Methods Data for aortic valve reinterventions (redo surgical aortic valve replacement, isolated redo aortic valve replacement, and valve-in-valve transcatheter aortic valve implantation, transcatheter valve-in-valve procedure) were collected (2010–2019). Logistic regression analysis was performed to identify pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…in those studies tended to undergo previous coronary artery bypass grafting more frequently (approximately 3% vs. 15-20%), which can confer a relatively higher risk for redo surgery (10,11). In addition, Deharo et al included patients with previous endocarditis (7).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…in those studies tended to undergo previous coronary artery bypass grafting more frequently (approximately 3% vs. 15-20%), which can confer a relatively higher risk for redo surgery (10,11). In addition, Deharo et al included patients with previous endocarditis (7).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…9 Moreover, compared with our patients, the patients in those studies tended to undergo previous coronary artery bypass grafting more frequently ($3% vs. 15-20%), which can confer a relatively higher risk for redo surgery. 10,11 In addition, Deharo et al included patients with previous endocarditis. 7 Recent meta-analyses that directly compared ViV-TAVI and surgery showed that the early 12 and mid-term 13 allcause mortalities were comparable.…”
Section: Commentmentioning
confidence: 99%